2003
DOI: 10.1080/713840400
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Transdermal Drug Delivery Systems for Diltiazem Hydrochloride

Abstract: Transdermal drug delivery system of diltiazem hydrochloride was developed to obtain a prolonged controlled drug delivery. Both the matrix diffusion controlled (MDC) and membrane permeation controlled (MPC) systems were developed. The matrix diffusion controlled systems used various combinations of hydrophilic and lipophillic polymers, whereas membrane permeation controlled systems were developed using the natural polymer chitosan. The MDC systems were prepared using the cast film method and the MPC systems by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 10 publications
(4 reference statements)
1
17
0
Order By: Relevance
“…DTH has been already investigated for transdermal delivery. 20,21 In the present study, PR patches were prepared with polyvinyl pyrrolidone (PVP) using DTH as drug model. These patches were evaluated for moisture content, water absorption, mechanical properties, in vitro drug release and in vitro skin permeation studies.…”
Section: Introductionmentioning
confidence: 99%
“…DTH has been already investigated for transdermal delivery. 20,21 In the present study, PR patches were prepared with polyvinyl pyrrolidone (PVP) using DTH as drug model. These patches were evaluated for moisture content, water absorption, mechanical properties, in vitro drug release and in vitro skin permeation studies.…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo permeation studies in rat model signified the prospective of this polymer to deliver effective concentration of drug for a prolonged period of time [46]. Several studies were also reported wherein chitosan-based hydrogel transdermal systems have been successfully utilized [47]. Hydrogels of this polymer prepared by physical crosslinking method were utilized for transdermal delivery of propranolol [48].…”
Section: Hydrogels For Transdermal Delivery Of Drugsmentioning
confidence: 99%
“…This drug delivery system of diltiazem HCL can be developed to deliver the drug so that a constant effective plasma drug concentration could be maintained for prolonged periods of time. Transdermal drug delivery system is a highly investigated drug delivery system of a number of drugs and many transdermal drug delivery systems of different drugs are commercialized 38 . This method provides many advantages over conventional administration including enhanced efficacy, increased safety, greater convenience and improved patient compliance.…”
Section: Transdermal Deliverymentioning
confidence: 99%